2012
DOI: 10.1088/0031-8949/85/04/045602
|View full text |Cite
|
Sign up to set email alerts
|

Torsional stability of carbon nanotubes filled with copper atoms

Abstract: Carbon nanotubes (CNTs) are frequently used as torsional devices in nanoelectromechanical systems; thus it is necessary to gain a thorough understanding of the mechanical behavior of tubes under torsion. In this paper, molecular dynamics simulations are carried out to investigate the torsional buckling of single-walled CNTs completely filled with copper atoms. Results show that, due to metal filling, the torsional rigidity of tubes can be dramatically enhanced and the critical torsional angles of filled tubes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 30 publications
7
9
0
Order By: Relevance
“…This observation is consistent with the results reported in earlier studies of Ref. [16,17] for the case of SWCNTs interacting with various gases and metals. For the case of freeform SWCNTs, the torsional stiffness of (10, 10) SWCNT has increased by 670% compared to that of (5, 5) SWCNT.…”
Section: Analysis Of Swcnt Torsion With Continuum Mechanics Theorysupporting
confidence: 93%
See 2 more Smart Citations
“…This observation is consistent with the results reported in earlier studies of Ref. [16,17] for the case of SWCNTs interacting with various gases and metals. For the case of freeform SWCNTs, the torsional stiffness of (10, 10) SWCNT has increased by 670% compared to that of (5, 5) SWCNT.…”
Section: Analysis Of Swcnt Torsion With Continuum Mechanics Theorysupporting
confidence: 93%
“…It can be noted from this figure that the maximum torque decreases while the torsional angle increases with the aspect ratio of the SWCNT, which is similar to results reported previously Ref. [15,16]. This is because SWCNTs with small aspect ratio are stocky and would require larger torque while SWCNTs with large aspect ratio are slender and can be twisted easily to large angles.…”
Section: Effect Of Surrounding Water Moleculessupporting
confidence: 89%
See 1 more Smart Citation
“…13 that prior to torsion, the fully-filled SWCNT can withstand more torque compared to that of an empty and half-filled SWCNT. This observation is consistent with the earlier reports of the torsional response of SWCNTs filled with SWCNTs [15], gases [17] and metals [16]. It is worth noting that when torsional strain is about 0.06, there is a sudden drop in torque of a fully-filled SWCNT in contrast to that of the empty and half-filled SWCNTs.…”
Section: Elastic Properties Of Capped Swcntsupporting
confidence: 92%
“…Their investigations revealed that the torsional responses of SWCNTs will be distinct which depends on the density and nature of the filling material. In addition, the torsional characteristics of CNTs filled with metals such as copper [16] and silicon atoms [17] have also been studied in the literature.…”
Section: Introductionmentioning
confidence: 99%